Implemetasi Pembangkt Listrik Tenaga Surya untuk Pengembangan Usaha Kebun Hidroponik PagiFarm - Soni Prayogi; Nita I Pertiwi; Arif Murti Rozamuri (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The increasing need for food and energy efficiency in the agricultural sector is a challenge for small businesses such as PagiFarm. This community service aims to implement solar power plants to support the development of hydroponic gardens at PagiFarm. The use of renewable energy is expected to reduce dependence on conventional electricity and increase the operational efficiency of the garden. The methods used include solar panel installation, technical training, and assistance in operating the system. The results of this program show that the use of solar panels can meet the daily electricity needs of hydroponic gardens and reduce operational costs by up to 30%. This implementation also increases awareness of the surrounding community about the importance of renewable energy in supporting agricultural businesses. In conclusion, solar power technology can be an efficient and sustainable solution for the development of small-scale agricultural businesses, while encouraging the adoption of environmentally friendly energy in the agricultural sector.